The Spell of Homo Informaticus: Two Superstitions and Three Dreams - Marius Povilas Saulauskas (Information Research: An International Electronic Journal)
Even at the dawn of a full-fledged information society Homo Informaticus as well as its netted counterpart - Homo Irretitus - already carries a handful of badly compatible fears and hopes. First, anxieties about an inevitable desolation of habitual patterns of human interaction and values,as well as an inexorably impending threat of horrifying global control. Second, evergreen optimism of rapidly approaching egalitarian era under the pledge of free universal access to information, cornucopian abundance of all imaginable material and spiritual goods, and unrestricted reign of knowledge once for all overthrowing unjust orders of power and brute force. The article puts under the close scrutiny the key pro et contra arguments involved in the theoretical articulation of these basic attitudes and examines the topical question: why can neither the dreadful fears nor the gay hopes of Homo Irretitus be reasonably sustained in the face of critical inquiry?